Presentations in Lectures to Prompt Innovations in Higher Education - N. A. Ostroglazova; N. V. Starostina (Высшее образование в России)
Considering the rich experience of using multimedia presentations as a teaching tool in higher education, in order to introduce new approaches and develop a methodology, there is a need to identify the strengths and weaknesses of existing practices, in particular to identify the emotional attitude of university students to existing lectures and presentations in the educational process and determine relevant opportunities to improve the practice of using interactive and visual educational tools.The empirical basis of the study was the results of a survey of students of 2–4 undergraduate courses at the Moscow State Institute of International Relations (University) of the Russian Ministry of Foreign Affairs in the 2019–2020 academic year. The survey involved 404 respondents. To process the obtained data, we used the Google Forms and Microsoft Office Excel programs, general scientific methods (comparison, generalization), statistical analysis methods, as well as content analysis.The empirical study showed a high level of student satisfaction with the volume and effectiveness of multimedia presentations used in the educational process, and also confirmed the theoretical ideas about the advantages and limitations of linear form presentations that dominate in the educational environment. Critical remarks included design errors, oversaturation of visual material, activity out of sync, and flaws in speaker behavior. Among the new techniques for working with presentation materials, photographing slides was noted. An important observation was the students’ request for self-sufficient visual materials of lectures and access to them.Prospects and opportunities for transforming familiar lectures and the learning environment as a whole were identified taking into account the existing experience of presentations at the university; ways of solving the problems with students’ perception and acquisition of material are proposed and specific recommendations are given for organizing a wide range of classes with visual and interactive components, today these are, first of all, remote online courses (MOOC, e-learning) and new forms of organization classroom activities (“flipped classroom”).